RETRACTED: Modeling techno-economic multi-objectives of smart homes considering energy optimization and demand management - Khan Mohammad Ahmar; Kareem A. K.; Askar Shavan; Abduvalieva Dilsora; R. Roopashree; Prasad K. D. V; Sharma Aanchal; Sharma Abhishek; Ghazaly Nouby M.; Mohmmedi M. (Science and Technology for Energy Transition)
Following the publication of the Retraction Notice, this article has been formerly retracted on 14 March 2025.